The John F. Kennedys : a family album - Shaw, Mark, 1922-1969. ([New York] Farrar, Straus, 1964)
Pictures of the family taken in Georgetown, Washington, D.C., Hyannis Port and elsewhere over a period of four years
Keywords: Kennedy family -- Portraits; Kennedy, John F. -- 1917-1963 -- Portraits; Kennedy family portraits -- Biography; Kennedy, John F. 1917-1963 Portraits -- Biography